The Maasai People: Initial investigations into public health practices of the Loitokitok District - Kelly, Lindsey (My University, 2010)
This field experience was an initial investigation to collect a baseline for community and environmental health of the Maasai people in Loitokitok District of southern Kenya, East Africa. This international community based experience was the first of a five year program through The School for Field Studies to address the public health concerns surrounding the group ranches in the area. Individuals who participated in the first year of the project were selected from graduate schools in the United States and Kenya. The Maasai, once a nomadic pastoralist people, were forced onto community group ranches and had to take up a more sedentary agro-pastoralist lifestyle. This development has had negative impacts on the health of the people and their livestock. In addition to the baseline surveys, healthcare facility evaluations and cultural coursework to understand the situations surrounding the Maasai were main focuses. A personal interview was conducted with the local veterinarian and district animal health and agriculture officer to learn more about the veterinary concerns faced in Loitokitok District. Data were collected using a multistage sampling for childhood immunization and morbidity history, household mortality, water and sanitation, health, food security and assets. Descriptive statistics were presented to local governmental officials, healthcare providers and community leaders to discuss their main health concerns once the data had been presented. The Maasai’s cultural and financial reliance on their livestock provides an opportunity for basic management changes in water quality and food security that will improve the overall health and sustainability of the people and their livestock. The additional four years of the project will be directed by the findings of these surveys and the concerns of the Maasai in the area.
Keywords: Public Health; Maasai; community health; environmental health; healthcare survey; healthcare Africa; Health Sciences, Hygiene (0568)